Вдосконалення методів пошуку найкоротших маршрутів на транспортній мережі - Прокудін, Георгій; Чупайленко, Олексій; Пилипенко, Юрій (Посвіт, 2019)
The article deals with the modified Dietskrey method for finding the shortest paths between all nodes of the transport network with the further representation of the transport problem in the classical matrix form. In the future, this will allow us to apply any of the known matrix methods for constructing optimal cargo transportation plans to solve it.
Improvement of methods of finding the shortest routes on transport networks
Keywords: 519.852.33; 656.073